Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-43897
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on Axial Compressor Stage Performance With Vortex Generators

Abstract: The performance of axial flow compressor stage can be improved by minimizing the effects of secondary flow and by avoiding flow separation. At higher blade loading, interaction of tip secondary flow and separated flow on blade surface is more near the tip of the rotor. This results in stall and hence decreases compressor performance. A previous study [1] was carried out to improve the performance of a rotating row of blades with the help of Vortex Generators (VGs) and considerable effects were observed. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Agarwal et al. 23 investigated a double vortex generator in a compressor stage, and the results showed that the use of vortex generators could affect the secondary flow at endwall of compressor, so as to enlarge the stall margin of compressor stage. The main mechanism of controlling flow separation by using vortex generator is to introduce the new vortex which has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal et al. 23 investigated a double vortex generator in a compressor stage, and the results showed that the use of vortex generators could affect the secondary flow at endwall of compressor, so as to enlarge the stall margin of compressor stage. The main mechanism of controlling flow separation by using vortex generator is to introduce the new vortex which has been widely studied.…”
Section: Introductionmentioning
confidence: 99%